Formulation and characterization of 5-fluorouracil and metformin biodegradable nanospheres for treating colon cancer - K. Bharathi Priya; K. Kulathuran Pillai; C. N. Nalini; Ubaidulla Udhumansha (SpringerOpen, 2024)
Abstract Background Cancer and diabetes mellitus are quite common diseases found together worldwide. A considerable amount of evidence is available for the rapid development and presentation of various types of cancer in the type 2 diabetes mellitus (DM2) population as compared with the population without diabetes. The objective of the study is to formulate and evaluate 5-fluorouracil (5-FU) and metformin (MET) nanoparticles (NPs) and to establish the characteristic features of the biodegradable NPs. 5-FU and MET NPs with chitosan as a biodegradable polymer were formulated by the ionotropic cross-linking method. 0.25 gm of MET and 0.25 gm of 5-FU were dissolved in 100 ml of distilled water, and stock solution was prepared. 5 ml of stock solution was slowly mixed into the chitosan solution to obtain the mixture of drugs and chitosan. The tripolyphosphate reserve liquid was dripped slowly into the chitosan solution with constant stirring until the opaline appearance was noticed in the mixture, then filtered, and dried. The NPs were evaluated for their physical properties and drug release kinetics. Cell proliferation assay was done using human colorectal carcinoma cell line (HCT 116). Results The formulation composed of 1.5 w/v of chitosan, 0.25 w/v of MET, and 5-FU had an average particle diameter of 198.7 nm. The polydispersity index was 0.757. Thermal and infrared spectroscopy results indicated the drugs and polymers selected for the formulation were unique without any identifiable interaction. The NPs were spherical in appearance, with numerous pours on the surface, which was evident when microscopically examined. Uniformity in drug release was observed, and the formulation demonstrated excellent release kinetics. HTC 116 cell line confirmed that the maximum percentage of cell death and minimum viability of cells were observed while using the combination of MET and 5-FU-NPs as compared to the pure MET or 5-FU alone. Conclusion MET and 5-FU-loaded chitosan NPs were found to have excellent physiochemical properties, particle size, and drug release from the polymer in a controlled manner. Half-maximal inhibitory concentration value (IC50) of MET and 5-FU-NPs was found to be significantly less as compared to MET and 5-FU alone or the combination.